Ibrexafungerp Demonstrates In Vitro Activity against Fluconazole-Resistant Candida auris and In Vivo Efficacy with Delayed Initiation of Therapy in an Experimental Model of Invasive Candidiasis - Wiederhold, Nathan P. (Antimicrob Agents Chemother, 2021)
Candida auris is an emerging pathogen that has rapidly spread to many countries on multiple continents. Invasive infections caused by this species are associated with significant mortality, and treatment options are limited due to antifungal resistance. Ibrexafungerp is the first-in-class member of the triterpenoids, which inhibit the production of (1,3)-β-d-glucan and can be administered orally. We evaluated the in vitro activity and in vivo efficacy of ibrexafungerp against C. auris. Antifungal susceptibility was tested by broth microdilution against 54 C. auris isolates. Neutropenic mice were intravenously infected with a clinical isolate, and a 7-day treatment course was begun 24 h postinoculation with vehicle control, ibrexafungerp (20, 30, and 40 mg/kg orally twice daily), fluconazole (20 mg/kg orally once daily), or caspofungin (10 mg/kg intraperitoneally once daily). Fungal burden was assessed by colony counts in the kidneys on day 8 and on day 21 or as mice became moribund in the survival arm. Ibrexafungerp demonstrated consistent activity, with MICs ranging between 0.25 and 2 μg/ml against all isolates. Marked improvements in survival were observed in mice treated with the higher doses of ibrexafungerp and caspofungin. Similarly, reductions in kidney fungal burden were also observed in these groups. No improvements in survival or reductions in fungal burden were observed with fluconazole, consistent with the in vitro resistance of the isolate used to establish infection to this azole. These results demonstrate that ibrexafungerp is effective in vivo against C. auris even when the start of therapy is delayed.